Site-level rehabilitation strategies for degraded forest lands - Sabogal, C. (ITTO, 2005)
The persistent physical, chemical and biological limitations found in degraded forest lands create barriers to natural forest regeneration; an accurate assessment of these factors is key in determining which rehabilitation interventions will be necessary, based on the objectives of the intervention, the landscape context and the available resources. This chapter focuses primarily on open or denuded forest lands which have been invaded by weeds, and also covers degraded areas affected by soil and water erosion.The prioritization of degraded forest lands for rehabilitation should take into account the location and condition of these lands, the interests of the stakeholders concerned, and the availability of resources for the restoration work. Priority areas comprise degraded areas that are affecting local people’s livelihoods, are important for biodiversity, and/or are causing environmental problems such as a decline in ecological functions. Thus, degraded areas on farmlands, areas of special ecological value, or areas that have been subjected to intensive extractive uses (such as mining) would all constitute priority areas for restoration. This chapter describes four strategies for the rehabilitation of degraded forest lands: protective measures; measures to accelerate natural recovery; measures to assist natural regeneration; and tree-planting. In addition, the application of agroforestry may be considered a fifth strategy for these areas. This strategy is dealt with in Chapter 12.